2019
DOI: 10.1177/2054358119867993
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Once- Versus Twice-Daily Tacrolimus Dosing on Medication Adherence in Stable Renal Transplant Recipients: A Canadian Single-Center Randomized Controlled Trial

Abstract: Background: Prevalence of immunosuppressant nonadherence in renal transplant recipients is high despite negative clinical outcomes associated with nonadherence. Simplification of dosing has been demonstrated to improve adherence in renal transplant recipients as measured through electronic monitoring and self-report. Objective: The purpose of this study was to replicate and extend previous findings by measuring adherence with multiple methods in a Canadian sample. Design: The study design was a randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…Their lifestyle, social roles and concepts of the world and identity are revised. The patient's attitude towards the disease also influences the active involvement in the therapy process by adherence to the appropriate frequency and time of taking medications, controlling their undesirable effects, and noting interactions (16). Therefore, it was justified to undertake the research to assess the degree of acceptance and identify the factors determining this parameter in renal transplant recipients, since the available literature has little data on this subject, and the obtained results may significantly optimize patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Their lifestyle, social roles and concepts of the world and identity are revised. The patient's attitude towards the disease also influences the active involvement in the therapy process by adherence to the appropriate frequency and time of taking medications, controlling their undesirable effects, and noting interactions (16). Therefore, it was justified to undertake the research to assess the degree of acceptance and identify the factors determining this parameter in renal transplant recipients, since the available literature has little data on this subject, and the obtained results may significantly optimize patient care.…”
Section: Discussionmentioning
confidence: 99%
“…A recent smaller randomized single-center study (n=38) using several adherence measurement methods confirmed better MEMS dose adherence (p=0.001) with the once-daily formulation of tacrolimus and a tendency toward better timing adherence (p=0.052) after 4 months. 65 MEMS day adherence and self-reported adherence (Transplant Effects Questionnaire, TxEQ) did not differ between formulations whereas medication possession ratio (MPR%) was significantly better in the QD group when measured dichotomously (p=0.044). 65 Other, uncontrolled or nonrandomized studies confirmed improvement in medication adherence in kidney, liver and heart transplant recipients after switching from a BID formulation to a QD formulation of tacrolimus.…”
Section: A C C E P T E Dmentioning
confidence: 91%
“…65 MEMS day adherence and self-reported adherence (Transplant Effects Questionnaire, TxEQ) did not differ between formulations whereas medication possession ratio (MPR%) was significantly better in the QD group when measured dichotomously (p=0.044). 65 Other, uncontrolled or nonrandomized studies confirmed improvement in medication adherence in kidney, liver and heart transplant recipients after switching from a BID formulation to a QD formulation of tacrolimus. [66][67][68][69] All these studies measured adherence uniquely by using self-report questionnaires (eg, BAASIS and others) but without electronic monitoring.…”
Section: A C C E P T E Dmentioning
confidence: 91%
“…However, clinical management with TAC therapy remains challenging due to its narrow therapeutic range and off-target effects on other organs, as well as the negative effect of long-term TAC use, including neurotoxicity, new-onset diabetes, and nephrotoxicity [ 15 , 16 ]. In addition, the twice-daily oral administration decreased patient adherence to TAC therapy [ 17 ]. Although new extended-release TAC formulations exist, TAC needs to be administered daily, and the trough level for maintaining optimal therapeutic targeting should be checked [ 18 ].…”
Section: Introductionmentioning
confidence: 99%